Farmers’ perception of area closure and its associated factors of participation in degraded grazing land restoration in Sedie-Muja Woreda, Northwest Ethiopia - Mebratu, Mulugeta Asmamaw; Getu, Kenu; Worku , Habtu (Journal of Degraded and Mining Lands Management, 2024)
In many parts of the world, degradation of grazing lands is one of the most important environmental issues. This study analyzed farmers’ perception of area closure and its associated factors of participation in degraded grazing land restoration in Sede-Muja Woreda, Northwest Ethiopia. A cross-sectional research design and a mixed research approach were applied in this study. The 384 sample respondents were randomly selected. Household surveys, interviews, focus groups, and field study techniques were used to acquire the data. A binary logistic regression model was used to identify the determinant elements that affect farmers' participation in the area closure of degraded grazing land restoration.  All of the total respondent farmers (100%) have a positive attitude towards multi-functionality benefits of area closures for local farmers. The model results show that the grazing experience (AOR = 2.981,95% CI = (1.143-7.775), access to safety net program (AOR = 2.787,95% CI = (1.146-6.77), access to livestock forage (AOR = 4.493,95% CI = (1.149-14.028), access to extension service (AOR = 2.522,95% CI = (1.917-6.6397), livestock ownership (AOR = 0.026,95% CI = (0.008-0.087), improved cattle breeds (AOR = 4.955,95% CI = (1.944-12.630), access to training (AOR = 3.169,95% CI = (1.409-7.131), farmers’ perception (AOR = 0.085,95%CL = (0.023-0.310), and communities’ consensus (AOR = 4.230, 95% CI = (1.377-12.996) were determinant factors that affect farmers' participation in the area closure of degraded grazing land restoration. To address the current grazing land degradation issues, every one of the relevant authorities as well as communities needs to work together to create modern grazing land management mechanisms such as grazing land enclosures, reduce animal size through improved cattle breeds, implement zero-grazing systems, and ensure the sustainability of existing enclosures.